Knowledge of, risk perception towards and reported preventive practices against Lassa fever among health workers in Ondo State, Nigeria (Journal of Ideas in Health, 2020)
Background: Secondary transmission of Lassa fever has been recorded annually among healthcare workers who provided care. An outbreak of the disease in Ondo State, Southwest Nigeria in 2018, recorded high morbidity and mortality. This study was conducted to assess the knowledge, risk perception, and preventive practices towards Lassa fever among healthcare workers.   Methods: A health facility-based descriptive cross-sectional study design was conducted involving senior members of staff randomly selected from the list of staff members. A structured pre-tested questionnaire was administered to 554 consenting respondents in 304 health facilities.Results: More than half of the respondents (317, 57.2%) are health workers in primary healthcare cadres. Although 444 (80.1%) knew the case definition for reporting, only 379 (68.4%) correctly indicated the reporting channel. Concerning risk perception, 174 (31.4%) rated their risk of contracting the disease in the workplace as high, and 309 (55.8%) indicated that hospitals' infection control policy is inadequate. Furthermore, only 76 (13.7%) of the respondents reported having modified their working habits for fear of being infected with Lassa fever three months before the study with 368 (66.4%) and 474 (85.6%) reported that they always use aprons and gloves respectively during treatment of patients.Conclusion: There is a need to strengthen the hospital infection control policy and train healthcare workers on reporting suspected cases.
Keywords: Lassa fever outbreak; Risk perception; Infection prevention practices; Healthcare workers, Ondo State, Nigeria